ANALISIS PENERAPAN BUDAYA ORGANISASI DI RUMAH SAKIT UMUM DAERAH SYARIFAH AMBAMI RATO EBU BANGKALAN - Sari, Miranti; Rosdiana, Weni (Jurnal Inovasi Administrasi Negara Terapan (Inovant), 2023)
Organizational culture research which in this study will later be better known as service culture, with the aim of analyzing the application of organizational culture in Syarifah Ambami Rato Ebu Bangkalan Hospital. This research is based on urgency which is reviewed from the point of view of organizational culture regarding the consistency of the implementation and application of ongoing organizational cultural values, as well as complaints regarding ongoing innovations, this is also based on the urgency link raised with the organizational culture theory used in this study . Furthermore, this research is a qualitative descriptive study, in which the population is all levels of employees at Syarifah Ambami Rato Ebu Hospital, with samples taken in the form of inclusion and exclusion criteria where inclusion criteria are appropriate criteria to become research subjects, intended the research carried out received appropriate sources and capacities related to the research being carried out. This study uses Stephen P. Robins' organizational culture theory with 7 indicators of organizational culture namely innovation and risk taking, attention to detail, attention to results, human orientation, team orientation, aggressiveness, and stability as well as 3 elements of organizational culture namely basic assumptions, values value, and artifacts. This research obtained results in the field that Syamrabu Hospital adheres to a service culture of "BERTASBIH", furthermore there are 5 indicators that still require further attention, these 5 indicators are attention to detail, namely the lack of understanding of employees regarding the service culture applied, result orientation related to understanding innovation what is not conveyed to patients is aggressiveness, namely related to time discipline, human orientation, namely related to workload and qualifications where sometimes there are still gaps, stability, namely the absence of regulations related to SOPs that should exist to monitor the ongoing evaluation of the service culture. Suggestions that can be made are internalization in the form of holding competitions between units or tiered socialization, re-evaluating workload and qualifications of employees, clarity of deadlines related to work assignments given, and the need to make SOPs related to evaluation and monitoring of the "BERTASBIH" service culture. Keywords: Analysis, Organizational Culture, Service Culture BERTASBIH, Syamrabu